Actualization of Karang Taruna in Implementing Entrepreneurial Values ​​in Drajat Village, Kesambi District, Cirebon City - Aji, Fathurrakhman; Ratnawati, Etty; Nurizzati, Yeti (Universitas Pendidikan Indonesia, 2024)
Problems that occur in the era of globalization and technological development often provide major challenges to the field of entrepreneurship in Indonesia. Moreover, in developing the economy, people are required to compete in running their entrepreneurship, so in this case the researcher conducted a study on the actualization of Karang Taruna Pangeran Drajat in implementing entrepreneurial values, as well as driving and inhibiting factors and strategies in its implementation, this is generally aimed at advancing business and the economy. Then the specific objectives of this study are: to find out and describe the actualization of Karang Taruna in implementing entrepreneurial values, driving and inhibiting factors, and the strategy of Karang Taruna Pangeran Drajat in actualizing entrepreneurial values. Internalization and realization of entrepreneurial values in Karang Taruna are very necessary, in this case it can make Karang Taruna have a strong entrepreneurial spirit and be able to compete in the current era of globalization and can play an important role in the economic development of the Drajat Village community. This research is a qualitative research with the technique used is a snippet of purposive sampling. Data collection techniques with interviews, observations and document analysis. Data validity uses data/source triangulation techniques and triangulation methods. Data analysis uses an interactive analysis model. Based on the results of the study, it can be concluded that the actualization of Karang Taruna Pangeran Drajat in implementing entrepreneurial values is: Able to see opportunities, optimism, able to take risks, creative and innovative, commitment, and proactive, these values are applied to every entrepreneurial activity. Then the driving and inhibiting factors in actualizing entrepreneurial values include, driving factors: environmental conduciveness, skills and knowledge, motivation and commitment, inhibiting factors: capital problems, managerial problems, business location problems. Then the strategy of Karang Taruna in implementing entrepreneurial values includes: education and training, communication and practice, believing in ability.